The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00011-004-1304-y
|View full text |Cite
|
Sign up to set email alerts
|

Marked decrease in the levels of two inflammatory markers, hs-C-reactive protein and fibrinogen in patients with severe carotid atherosclerosis after eversion carotid endarterectomy

Abstract: Our present findings indicate that removal of atherosclerotic plaques from the carotid arteries markedly decreases the production of two acute phase proteins due to the decrease of the inflammatory burden or the removal of the advanced plaques able to produce these proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Patients included in the present study represent a subgroup of a prospective study of 123 consecutive patients, in which MBL2 genotypes, 9 changes in CRP 16 and C3 10 levels were previously published. The reason for including less patients in the present study was the limited availability of the serum samples, otherwise the study setup was the same.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients included in the present study represent a subgroup of a prospective study of 123 consecutive patients, in which MBL2 genotypes, 9 changes in CRP 16 and C3 10 levels were previously published. The reason for including less patients in the present study was the limited availability of the serum samples, otherwise the study setup was the same.…”
Section: Methodsmentioning
confidence: 99%
“…The reason for including less patients in the present study was the limited availability of the serum samples, otherwise the study setup was the same. 9,10,16 Briefly, all patients underwent eversion type CEA: the surgical technique has been described earlier. 17 The indication for CEA was in accordance with the American Heart Association guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…32 Nevertheless, the removal of atherosclerotic plaques from the carotid arteries markedly decreases the production of high sensibility-CRP and fibrinogen, probably because of the decrease in the inflammatory burden or the removal of the advanced plaques able to produce these proteins. 33 At present, there is not sufficient evidence to recommend measurement of CRP in the routine evaluation of cerebrovascular disease risk in primary prevention.…”
Section: Systemic Markers Of Atherosclerotic Inflammatory Processesmentioning
confidence: 99%
“…The earlier studies showed that fibrinogen and its degradation products are involved in the development of atherosclerosis by mediating inflammatory responses and participating in thrombosis formation [15-19]. Fibrinopeptide A (FPA) is a peptide of 16 amino acids which occurs as a natural consequence of hemostasis from proteolysis of fibrinogen’s Aα chain [20].…”
Section: Introductionmentioning
confidence: 99%